Leitura de texto literário: a gamificação digital como dispositivo para a compreensão da obra O quinze - Sena Júnior, Flávio Brito de (2024)
This research presents a study on the contribution of gamification, as an intervention device for reading and understanding the literary text, O Quinze, by Raquel de Queiroz. To this end, the general objective was to analyze the interactive coherence and production context of this work, with regard to enunciative mechanisms, within a socio-discursive interactionist reading teaching perspective, using gamification as an intervention device for text reading. literary. With this purpose in mind, the theoretical-methodological current chosen was sociodiscursive interactionism (ISD), which is based, for treatment with the text, on both the socio-historical-cultural context of the actors involved in reading and the conditions of production. of the text, having in the studies of Bronckart (1999, 2023) and Neves (2011), with regard to enunciative mechanisms, the reference basis for the analysis of voices and modalities, respectively. Regarding analyzes focused on reading perspectives and levels of comprehension, the analyzes were based on studies by Marcuschi (2008) and Menegassi (1995), in that order. The method used was action research, in which nine students, from a state school in the state of Ceará, were involved in the research, three students, of both sexes, representing each of the high school grades. The methodological path lasted the 2023 academic year and had two moments: reading the work and gamified reading activity. At first, reading activities were carried out. In the second moment, gamification was used as a data generation tool. After carrying out these procedures, the analysis turned to the students' subjective responses. The relationship between voices and modulators and the identification of enunciative positions, the reading perspective and the level of understanding were taken into consideration. From this analysis, it was verified that gamification contributed to student understanding at the literal, inferential, interpretative and improper levels. However, it is clear that the level of interpretative understanding was not presented in a similar way for all students and, therefore, it is concluded that gamification, as an intervention device for reading and understanding literary texts, did not contribute to all students reached the level of critical understanding.